Bezpieczeństwo ekologiczne i zrównoważony rozwój w aspekcie Strategii Bezpieczeństwa Narodowego Rzeczypospolitej Polskiej - Mariusz Ciszek (Studia Ecologiae et Bioethicae)
Ecological threats awaken fear among not only lovers of nature, but also more and more often among politicians and experts concerned with national safety and international problems. This situation can also be encountered in Poland. Ecology, however, is not a priority here, although environment protection and the problems it faces appear in different state documents. The present article is concerned with the issue of ecological safety in reference to the conception of national safety. This was mainly based on the Strategy of the National Safety of the Polish Republic which has been in force since 2007. An outline of the problems concerning the evolution of ecological safety in Polish national safety strategies has also been presented. According to the analysis of the contents of the mentioned documents, the article refers to the conception of development which is also closely connected with ecological safety.